SpaceX Requests Starlink Gen2 Modification, Previews Gigabit-Speeds - Jewett, Rachel (Satellite Today, 2024)
According to the filing, SpaceX seeks authority to use its authorized frequency ranges in the Ku-, Ka-, V-, and E-band for both fixed-satellite service (FSS) and mobile-satellite service (MSS) in frequency ranges that share allocations for both FSS and MSS. EPFD limits were the subject of a lot of discussion around the WRC-23 spectrum conference from both Geostationary (GEO) and Non-Geostationary Orbit (NGSO) operators. According to the filing, reducing the nominal inclination to leverage Starship for Starlink launches more quickly.